THE ROLE OF THE DIGITAL ECONOMY IN THE DEVELOPMENT OF THE ENERGY AND OIL AND GAS SECTORS OF THE REPUBLIC OF UZBEKISTAN (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This paper examines the impact of the digital economy on the development of the energy and oil and gas sectors of the Republic of Uzbekistan in the context of implementing the national socio-economic development strategy and the long-term “Uzbekistan–2030” program. The study highlights the role of digital technologies in improving management efficiency, optimizing production processes, and strengthening the investment attractiveness of strategic industries. Based on an analysis of theoretical approaches and practical trends, it is shown that digitalization acts as a key driver of sustainable economic growth and international competitiveness. The paper formulates conclusions and practical recommendations for the further development of digital transformation in the country’s energy and oil and gas sectors.
Keywords: Digital economy, digitalization, energy sector, oil and gas industry, investment, economic growth, innovation, management, sustainable development, Uzbekistan-2030.